Penguatan Kapasitas Sumber Daya Pengawas Kelurahan dan Desa (PKD) dalam Rangka Pengawasan Rekapitulasi Suara pada Pemilu Tahun 2024 di Kecamatan Montong Gading - Widya Hartati; Sandy Ari Wijaya; Ratna Yuniarti; Salmi Yuniar Bahri; Nova Hari Santhi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In the midst of the political and technical dynamics of holding the 2024 simultaneous elections, the role of election observers has become increasingly vital. Election supervision must ensure that the entire process, from campaigning to vote counting and recapitulation, is carried out in accordance with applicable regulations. This not only requires a deep understanding of laws and regulations, but also the ability to detect and address possible violations. The method used in this technical guidance is starting with preparation for the implementation of the technical guidance until implementation by providing various materials related to election supervision which will be carried out by Subdistrict/Village supervisors in 8 (eight) villages in Montong Gading District, East Lombok Regency. The implementation of technical guidance has been successful and has been successful in increasing participants' understanding, skills and readiness in carrying out supervisory duties at sub-district/village level in Montong Gading District, East Lombok Regency.